2021
DOI: 10.1371/journal.pone.0260669
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of tuberculosis treatment interruption among patients in Vihiga County, Kenya

Abstract: Background Despite robust Tuberculosis (TB) program with effective chemotherapy and high coverage, treatment interruption remains a serious problem. Interrupting TB treatment means that patients remain infectious for longer time and are at risk of developing drug resistance and death. This study was conducted to identify and describe predictors of TB treatment interruption. Methods A cohort of 291 notified TB patients from 20 selected health facilities in Vihiga County were enrolled in to the study and follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…To reduce loss to follow-up in male patients, measures should be taken to improve their knowledge of tuberculosis, as well as improve family and economic support. 21,22 It was reported in many studies that aging was a risk factor for an unfavorable outcome of MDR-TB treatment; 13,16,21,23 it is due to older people may combine other diseases and suffer more from drug side effects or death. 24 In this study, 40% of the patients were older than 40 years old, indicating that a considerable number of patients are at risk of unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce loss to follow-up in male patients, measures should be taken to improve their knowledge of tuberculosis, as well as improve family and economic support. 21,22 It was reported in many studies that aging was a risk factor for an unfavorable outcome of MDR-TB treatment; 13,16,21,23 it is due to older people may combine other diseases and suffer more from drug side effects or death. 24 In this study, 40% of the patients were older than 40 years old, indicating that a considerable number of patients are at risk of unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There were also some limitations in our study. Some studies showed that smoking and drinking were risk factors for unfavorable outcomes, 21,22,32 but we did not involve these factors. China is a country with a high burden of tuberculosis and HIV, but there were only 2 HIV-positive cases in our study.…”
mentioning
confidence: 99%
“…We found 7 studies showed low income and experienced loss of job as a significant factor of adherence (12,16,(23)(24)(25)(26)(27), 6 studies for comorbidities (16,(28)(29)(30)(31), and 2 studies for age/ elderly (25,28), and 2 studies for the level of education (16,32). TB patients with low income have difficulty paying for transportation costs to health services and also face a lack of food during treatment (12,13,27,32). TB patients with comorbidities such as depression, diabetes mellitus, and HIV are more noncompliant with TB medication.…”
Section: Individualmentioning
confidence: 95%
“…The sociodemographic of individual factors found that low income, comorbidities, age, and education level impact TB medication compliance. We found 7 studies showed low income and experienced loss of job as a significant factor of adherence (12,16,(23)(24)(25)(26)(27), 6 studies for comorbidities (16,(28)(29)(30)(31), and 2 studies for age/ elderly (25,28), and 2 studies for the level of education (16,32). TB patients with low income have difficulty paying for transportation costs to health services and also face a lack of food during treatment (12,13,27,32).…”
Section: Individualmentioning
confidence: 98%
See 1 more Smart Citation